2019
DOI: 10.1002/mnfr.201801341
|View full text |Cite
|
Sign up to set email alerts
|

Alkylpyrazines from Coffee are Extensively Metabolized to Pyrazine Carboxylic Acids in the Human Body

Abstract: Scope: Coffee is a complex mixture of over 1000 compounds, including diverse heteroaromatic compounds such as alkylpyrazines. Little is known about the intake, metabolism, and bodily distribution of these compounds. Therefore, a human intervention study is conducted to investigate the excretion of alkylpyrazine metabolites in urine after the ingestion of brewed coffee containing alkylpyrazines. Methods and results: After consuming a diet without heat-processed food, ten volunteers consumed 500 mL of freshly br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…2-methylpyrazine was the most abundant compound among the pyrazines group in the experiment. This is in agreement with the results of Kremer et al [31], who reported a range of concentration of the aromatic compound in coffee from 34.8 ppm to 91.6 ppm. The mean value in our study was 47.9 ppm, the overall range was between 1.0 and 121.5 ppm (µg/g).…”
Section: Aromatic Alkyl Pyrazinessupporting
confidence: 93%
“…2-methylpyrazine was the most abundant compound among the pyrazines group in the experiment. This is in agreement with the results of Kremer et al [31], who reported a range of concentration of the aromatic compound in coffee from 34.8 ppm to 91.6 ppm. The mean value in our study was 47.9 ppm, the overall range was between 1.0 and 121.5 ppm (µg/g).…”
Section: Aromatic Alkyl Pyrazinessupporting
confidence: 93%
“…It can therefore be deduced that the rest remains in spent coffee grounds. In humans, alkyl pyrazines are metabolized to their corresponding carboxylic acids and almost completely excreted renally [139]. Spent coffee grounds are susceptible to contamination with mycotoxins, therefore Iriondo-DeHond et al investigated this.…”
Section: Spent Coffee Groundsmentioning
confidence: 99%
“…Pyrazine analogues are also present in a variety of other heat-treated foods, , such as in coffee where 2-methylpyrazine and 2,5-dimethylpyrazine are present as important aroma compounds; the difference compared with M12-M14 is the different types of aminoketones for hererocyclization, so the pyrazine-derived compounds may or may not be specific for intake of deep-fried potatoes; however, this has to be further investigated.…”
Section: Discussionmentioning
confidence: 99%